DETERMINAN NILAI PELANGGAN DAN PENGARUHNYA TERHADAP POSITIVE WOM PADA PENGGUNA SHOPEE DI DAERAH ISTIMEWA YOGYAKARTA - Elsi Maya Intan; Joko Setyono (Universitas Lancang Kuning, 2023)
This study aims to identify the determinants of customer value and its effect on positive WOM on shopee users in DIY. The model built includes six variables, four independent variables and two dependent variables. Variables that have positions as independent variables are reputation, advertising attractiveness, testimonials, and ratings. variables that act as dependent variables are customer value and Positive WOM. Data analysis was carried out using the Canonical Corelation Analysis approach. The data used are primary, quantitative, and cross-sectional data. Data were collected from 240 respondents by distributing questionnaires using a Likert scale with five answer choices. Data analysis was carried out with the help of the SPSS 23 For Windows application. Based on the results of tests that have been carried out using the canonical correlation test or multivariate test (MANOVA), seen from the test results there are significant values in groups but not individually, then continued with canonical weight and canonical loading tests to measure how far or how big X ( reputation, advertising attractiveness, testimonials and ratings) affect Y1 (customer value) and Y2 (positive WOM). In canonical weight Y1 has a value of 0.31262 and Y2 has a value of 0.58776. in the canonical loading table, it is known that the value of Y1 is 0.31661 and Y2 is 0.75826. Judging from the results that there is a significant group and loading but not individually and in weight. This means that reputation has little effect on Y1 (customer value) and Y2 (positive WOM) for shopee users in DIY.